Cash Waqf for Developing Islamic Economy: Case Study in Indonesia - Aam Slamet Rusydiana; Yayat Hidayat; Tika Widiastuti; Solihah Sari Rahayu (Universitas Negeri Surabaya, 2021)
This study attempts to identify the causes and dominant factors that hinder the development of cash waqf in Indonesia, using the IFE-EFE Matrix and SWOT methods, while offering solutions to solve it. Based on the results of IFE analysis, the highest-rank of strengths is the ability of cash waqf in expanding the base of waqf fund sources followed by the ease and zero cost of funds. In comparison, the top weaknesses are the lack of socialisation to the community and the lack of professional nazhir human resources. The results of EFE analysis imply the highest-rank opportunity is the potential of unlimited cash waqf followed by the emergence of many sharia financial institutions and Islamic economics study programs in universities. Meanwhile, the top threat is a weak political will of authorities, followed by the majority of traditional nazhir. It is expected that there will be a joint commitment from various parties, both from policymakers and academics and practitioners to support and encourage efforts to develop the Islamic (social) finance industry, especially in developing cash waqf in Indonesia.